Legal Problems Involving the Illegality of Administrative Order That is Explicit and Serious Error - Moonma, Uncharika (Naresuan University Law Journal, 2015)
The judgment of the Supreme Administrative Court, No. Or. 47/2546 in case of government organization issuing administrative order mandating the official who infringes the government organization to compensate pursuant to Section 12 of the Act on Liability for Wrongful Act of Officials, B.E. 2539 (A.D. 1996) without actual infringement or serious negligence of such official pursuant to Section 10 in supporting with Section 9 of the above mentioned act. Such order was thus considered as explicit and serious error and deemed as it was not issued. Judgment of NakhonRatchasima Administrative Court by comment of the Administrative Procedures Committee and comment of the Council of State had applied rules regarding Explicit and Serious Error administrative order according to the judgment of such Supreme Administrative court to comparatively consider the case. Since the Act on Liability for Wrongful Act of Officials, B.E. 2539 (A.D. 1996) had no any provision about explicit and serious error administrative order nor void whatsoever but there is only the provision to repeal those illegality administrative order. The author therefore study to determine that at what extent which the explicit and serious error administrative order would be regarded as administrative order is not issued and what is its legal effect. From the study and analysis, it is found that cause of explicit and serious administrative order was caused by such order was substantive illegal due to issuance of order that significantly conflict against the law, it was not correspond with other related law and due to the failure of existing fact. In addition, it is also caused by unlawful order in term of its procedure, namely, failure about the ability of the person duly empowered to issue administrative order. Result of explicit and serious error administrative order is it could not reveal any result as required by the issuer. The administrative is thus unable to enforce such administrative order. In addition, such explicit and serious administrative order shall in no way become effective regardless how long of time is lapsed. In principle, the beneficiary may refer the absence of such order at any time and should there is any explicit and serious error administrative order, even it is not referred by the parties, the administrative court may refer it for consideration and judge to indicate invalidity of such order.